Temperature and water stress during conditioning and incubation phase affecting Orobanche crenata seed germination and radicle growth - Moral, Juan; Lozano-Baena, María Dolores; Rubiales, Diego (Frontiers in Plant Science, 2015)
Orobanche crenata is a holoparasitic plant that is potentially devastating to crop yield of legume species. Soil temperature and humidity are known to affect seed germination, however, the extent of their influence on germination and radicle growth of those of O. crenata is largely unknown. In this work, we studied the effects of temperature, water potential (Ψt) and the type of water stress (matric or osmotic) on O. crenata seeds during conditioning and incubation periods. We found that seeds germinated between 5 and 30ºC during both periods, with a maximum around 20ºC. Germination increased with increasing Ψt from -1.2 to 0 MPa during conditioning and incubation periods. Likewise, seed germination increased logarithmically with length of conditioning period until 40 days. The impact of the type of water stress on seed germination was similar, although the radicle growth of seeds under osmotic stress was lower than under matric stress, what could explain the lowest infestation of Orobanche spp. in regions characterized by saline soil. The data in this study will be useful to forecast infection of host roots by O. crenata.